Algoritmo de optimización en redes de distribución aérea de baja tensión, caso de análisis EMPRESA ELÉCTRICA CENTRO SUR C.A. - Sanchez Cueva, David Andres (2023)
The purpose of this research is to evaluate and optimize existing secondary networks within the concession area of the electrical company CENTROSUR. The aim is to reduce costs by reusing network elements and achieving voltage drop values below permissible limits. To do this, information related to low-voltage overhead distribution networks is collected. Then, internal files of the electrical company CENTROSUR are considered to analyze the topology and configuration of existing networks, highlighting their main characteristics and proposing a procedure for calculating voltage drop. There is a difference between networks in urban and rural areas, making it impossible to consider a standard network to represent both. Therefore, the most feasible approach for this process is to analyze branches from the transformer center to the end. To optimize existing networks, an algorithm is developed in the MATLAB software, and to verify its operation, an existing network in the Azuay province in the city of Gualaceo is considered. The results are based on processes, conditions, and suggestions entered into the program. These solutions not only allow the user to comply with what is available but also provide important information for decision-making and economic as well as technical benefits. In this case, it is possible to reuse the existing transformer and its location, avoiding the need to change a pole and extend medium voltage lines. Keywords: Secondary network optimization, center of mass, low-voltage network reconfiguration, CENTROSUR, voltage drop.